The fundamental systems in a modern constructed municipal solid waste / Elias Mohd Den and Khairi Khalid - Mohd Den, Elias; Khalid, Khairi (2006)
The volume of municipal waste generated is mainly attributed to the increase in population. In Malaysia, landfilling sites for the disposal of MSW are rarely operated ill a sanitary manner. They are basically an uncontrolled open dumping sites rather than a properly engineered sanitary landfill and with a population of more than 20 million and a waste generation rate of 1kg/capita/day is going to generate an enormous amount of volumetric solid waste in years to come one of the pressing problems facing municipalities is a safe and a long disposal of waste in a landfill which control and minimize the environmental problems created such as air pollution and the possibility of ground water contamination due to liquid leachate. This paper deals only with the fundamental systems in an engineered constructed MSW landfill to contain the above problems. These are leachate containment system (barrier), leachate collection and drainage systems, landfill gas management system and finally the cover (cap) system. It should be emphasized here that this is only a mere general overview and discussion of a practical as well as theoretical should be of a modern MSW landfill.